2018
DOI: 10.11005/jbm.2018.25.3.153
|View full text |Cite
|
Sign up to set email alerts
|

Linkage of Fibroblast Growth Factor 23 and Phosphate in Serum: Phosphate and Fibroblast Growth Factor 23 Reduction by Increasing Dose of Sevelamer

Abstract: BackgroundHigh serum phosphate and fibroblast growth factor-23 (FGF-23) levels are well-recognized independent risk factors of mortality and morbidity in patients with chronic kidney diseases (CKDs). Sevelamer, as a phosphate chelating agent, reduces serum phosphate and FGF-23 levels produced by bone osteocytes. This study aimed to determine the best dose at which sevelamer could successfully reduce serum phosphate and FGF-23 levels in rat models of adenine-induced CKD.MethodsCKD was induced using adenine. Hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Another argument to be looked at with caution is that, although not statistically significant, in our study we observed in the group with VC a higher calcium-based phosphate binders intake and lower non-calcium-based phosphate binders intake, resulting in better phosphorous control in that group. In clinical trials for the pharmacological management of phosphate imbalance, phosphate binders, especially non-calcium-based phosphate binders, were reported to low serum phosphorous levels by decreasing fibroblast growth factor-23 (FGF-23), which has been shown to stimulate phosphorous excretion and reduce VC [ 68 ] with protective effects on VC [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another argument to be looked at with caution is that, although not statistically significant, in our study we observed in the group with VC a higher calcium-based phosphate binders intake and lower non-calcium-based phosphate binders intake, resulting in better phosphorous control in that group. In clinical trials for the pharmacological management of phosphate imbalance, phosphate binders, especially non-calcium-based phosphate binders, were reported to low serum phosphorous levels by decreasing fibroblast growth factor-23 (FGF-23), which has been shown to stimulate phosphorous excretion and reduce VC [ 68 ] with protective effects on VC [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…At all phases of CKD, hyperphosphataemia is a generally acknowledged risk factor for mortality and cardiovascular disease [ 85 ]. It was also reported that the blood P levels increased in adenine-induced CKD rats [ 86 ]. Bifidobacteria produce SCFA and makes the intestinal lumen more acidic and, therefore, enhances Ca ionisation.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphate binders have been shown to reduce serum phosphorus levels by decreasing FGF23, which accelerates phosphorus excretion and prevents vascular calcification. Compared to calcium phosphate binders, a recent randomized study showed that the phosphate binder sevelamer reduced mortality more in elderly hemodialysis patients [ 210 , 211 ].…”
Section: Translational Opportunitiesmentioning
confidence: 99%